Public Learning and Private Learners: The Separation of Public and Private in Renaissance Literature and Pedagogy - Carlson, Eric (History compass, 2012)
Although Michael McKeon’s The Secret History of Domesticity is both a major achievement in public sphere theory and builds a major bridge between studies of the Restoration and the Renaissance, it also suggests a further examination of evidence from before the civil wars. While the opening chapter considers the pre-16th-century developments of privacy in politics, economics and religion, the book’s literary and cultural evidence focuses overwhelmingly on the 17th and 18th centuries. Taking the topic of education as the main point of departure, this article argues that the conceptual separation of public and private can be seen in Tudor evidence such as Richard Mulcaster’s pedagogy manual, Positions (1581), Dudley Fenner’s Artes of Logike and Rhethorike (1584) and even in the statutes of London’s Gresham College (1596). Although the language of public and private in these texts is inchoate and provisional, these Elizabethan educational texts also participate in what McKeon identifies as the emergence of the modern categories of publicity and privacy.